Cultural Factors Contributing to Maternal Mortality Rate in Rural Villages of Limpopo Province, South Africa - Marabele PM; Maputle MS; Ramathuba DU; Netshikweta L (Dove Medical Press, 2020)
Portia Maphale Marabele, Maria Sonto Maputle, Dorah Ursula Ramathuba, Lizzy Netshikweta Department of Advanced Nursing Science, University of Venda, Thohoyandou, South AfricaCorrespondence: Maria Sonto MaputleDepartment of Advanced Nursing Science, University of Venda, Private Bag X5050, Thohoyandou 0950, South AfricaTel +27 15 9628125Fax +27 866671337Email sonto.maputle@univen.ac.zaIntroduction: The understanding of the link between cultural affairs and maternal health is critical to save the lives of women. The South African maternal mortality rate (MMR) target for 2015 was 38/100,000 live births. In 2017, South Africa had 1,222 maternal deaths. The purpose was to determine the perceived cultural factors contributing to MMR in rural villages in Mopani District.Methods: This qualitative research and non-probability purposive sampling was used to select participants who met the inclusion criteria. Thirty women, age 40 years and above childbearing age, who had given birth in their lifetime, were sampled. Data were collected through in-depth individual interviews at the women’s homes. Probing to elicit more information was conducted focusing on hemorrhage, hypertension and risk of contracting human immunodeficiency virus (HIV). Data were analyzed through open coding methods. Trustworthiness was ensured by Guba and Lincoln’s criteria, credibility, dependability, confirmability, and transferability.Results: From the study three themes emerged from the data as cultural factors relating to heavy, red post-delivery bleeding perceived as cleaning-out of the womb. With hypertension, gaining weight rapidly before the 20th week of gestation not reported as a pregnancy was still culturally concealed. Contracting HIV, women were exposed to unsafe sex practices due to cultural expectations of having children as a sign of femininity.Discussion: The formulation of culture congruent interventions to promote good and acceptable cultural practices that cannot harm the physical and mental status of women was recommended to reduce unplanned deaths among them.Keywords: hemorrhage, human immunodeficiency virus, hypertension, maternal mortality rate, perceived cultural factors